Preferences in the use of electronic payments in Ecuador - Rubio, Jeniffer (2021)
Over the years, the importance of adopting electronic means of payment for the benefit of individuals and the economic activity of the countries has become evident worldwide. In this paper, using the National Survey of Employment, Underemployment and Unemployment (ENEMDU), through a logistic model, the main factors that influence Ecuadorians in the use of electronic means of payment are identified. Characteristics such as age, education, income, area, financial education and region determine theprobability of using electronic means of payment in Ecuadorian households. The results obtained reflect the importance of implementing financial inclusion policies and promoting the use of electronic means of payment.